Effect of rare earth Eu on microstructure and properties of Al-Mg-Si-Fe alloy - CHEN Haiyan; PAN Meishi; DENG Quanwei; LONG Xie; HUANG Xiaohan; WANG Chao (Cailiao gongcheng)
Developing aluminum alloys with high strength， high conductivity， and thermal conductivity is the key to applying aluminum alloy materials in electrical， electronic， and heat dissipation industries. Aiming at these requirements， the effect of adding trace Eu to Al-Mg-Si-Fe alloy on the microstructure and properties of vacuum die-casting products are systematically studied. The results show that the alloy modification effect of adding 0.05%-0.25% （mass fraction/%， the same below）Eu first increases and then decreases. When adding 0.15%Eu， the grain is significantly refined， and the precipitation of the brittle （FeSiAl） eutectic phase and long plate-like eutectic Si in the alloy is restrained. The solid solubility of Mg in the aluminum matrix is reduced， and the lattice distortion of the alloy is reduced. Therefore the mechanical properties， electrical conductivity， and thermal conductivity of the alloy have been improved simultaneously. The Al-Mg-Si-Fe-0.15Eu alloy has a thermal conductivity of 68.50 mm2/s， electrical conductivity of 51.4% ICAS， tensile strength of 148 MPa， and elongation of 16.20%. Compared with the original Al-Mg-Si-Fe cast alloy， the thermal conductivity increases by 12.50%， the electrical conductivity increases by 1.4% ICAS， the tensile strength increases by 20 MPa， and the elongation increases by 5.40%. The tensile fracture morphology of the alloy changes from quasi-cleavage fracture to ductile fracture.